2006
DOI: 10.3148/67.1.2006.7
|View full text |Cite
|
Sign up to set email alerts
|

Primary Food Sources of NutrientsIn the Diet of Canadian Adults

Abstract: We must understand the contributions of foods to nutrients, and distinguish "important" sources of nutrients (those consumed by many in substantial amounts) from "good" sources (foods rich in particular nutrients, whether eaten or not).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…protein, vitamin D, calcium, etc. ), and significantly contributes to total daily nutrient intakes [5]. However, enhancing the population's eating habits remains an important public health challenge and identifying factors that promote the consumption of healthy foods (such as milk and alternatives) constitutes a first step.…”
Section: Introductionmentioning
confidence: 99%
“…protein, vitamin D, calcium, etc. ), and significantly contributes to total daily nutrient intakes [5]. However, enhancing the population's eating habits remains an important public health challenge and identifying factors that promote the consumption of healthy foods (such as milk and alternatives) constitutes a first step.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed their widespread use in children (Northstone and Emmett, 2005;Alexy et al, 2008;Pryer and Rogers, 2009), adolescents (Milligan et al, 1998) and adults (Pryer et al, 2001;Johnson-Down et al, 2006) in western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing that postprandial hyperlipidemia and hyperglycemia is a cardiovascular risk factor (O'Keefe & Bell, 2007), the potential health importance of MAG GEL is obvious, as is the need to assess the acute postprandial responses to major dietary fat products such as butter, margarines, and oils (Johnson-Down et al, 2006). Previous studies have concentrated on the responses of metabolic and cardiovascular risk variables to chronic replacement of dietary cooking and food preparation fat with various spreads such as margarines and butter (Judd et al, 1998;Lichtenstein et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The primary dietary fat sources for adult Canadians are butter, margarine, and oil (Johnson-Down, Ritter, Starkey, & Gray-Donald, 2006). Butter maintains its spread consistency and structure primarily due to its saturated fat content, and traditional manufacturing processes for other spreads, margarines, and shortenings utilize hydrogenation and/or saturated fats to achieve the desired structuring of liquid oil into semi-solid plastic pastes.…”
Section: Introductionmentioning
confidence: 99%